An Oxidative Stress Study on Curcumin and NanoCurcumin against Aluminum Phosphide-induced Kidney Injury in Rats: The Role of SIRT1/FOXO3 Signaling Pathway in Nephrotoxicity - Ghasemi, Hassan; Manesh, Seyde F. M.; Kheiripour, Nejat; Asl, Sara S.; Jouzdani, Ali Fathi; Ranjbar, Akram; Abdolvahab, Mohadeseh Haji (Pharmaceutical Nanotechnology, 2024)
Introduction: In this study, we have investigated the aluminium phosphide (ALP) toxicity on Renal Function and oxidative stress in kidney tissue of male rats and the possible protective role of Curcumin and nanoCurcumin against ALP-induced nephrotoxicity. Methods: Thirty-six adult male rats were divided into 6 groups (n=6). ALP (2 mg/kg oral administration) and control groups received Curcumin and nanoCurcumin (oral administration 100 mg/kg) or without it. After seven days of treatment, kidney parameters, oxidative stress biomarkers, and expression level of sirtuins1 (SIRT1)/Forkhead box protein O1 (FoxO1) pathway genes were evaluated in kidney tissue. In addition, histopathological changes in the kidney tissues were assayed. Results: In the ALP group, compared to the control group, lipid peroxidation levels, urea, and creatinine were increased, and total antioxidant capacity and thiol groups decreased significantly p < 0.05. In Curcumin and nanoCurcumin groups compared to the ALP group, lipid peroxidation and creatinine decreased significantly p < 0.05. Also, Curcumin and nanoCurcumin improved the tissue damage caused by ALP. NanoCurcumin modulated the effect of ALP on the gene expression levels in SIRT1/FoxO1. Conclusion: The present study showed that ALP intoxication in kidney tissue can induce oxidative damage. Moreover, Curcumin and nanocurcumin, as potential antioxidants, can be effective therapeutics in ALP-induced nephrotoxicity.
Keywords: nanocurcumin